Stigmatization of «haber» agreement - Martel Paredes, Víctor Arturo (2020)
The purpose of this paper is basically to give an account about a grammatical form produced within the logic of a natural language as Spanish, specifically, agreement between haber and a plural NP. This construction nevertheless is censured with the interest of prestigious and traditional forms, which, across the centuries, grammarians tried unsuccessfully to impose in frequent speech and writing, on grounds of notions of grammaticality that, in fact, do not represent the inner grammar of speakers.